Facilitating social work role plays in online courses: The use of video conferencing - Dale Fitch (Advances in Social Work, 2016)
Role plays have served an instrumental role in social work education by providing opportunities for students to acquire interaction skills. This project tested various online video conferencing tools to facilitate role plays for students who live in different locations and who are unable to be at the same place at the same time. Key features of the technology included the ability to facilitate real-time interaction, compatibility with laptops and Wi-Fi connections, and the ability to record sessions for later viewing and feedback. Method: Case study design. Results: Students were able to use the videoconferencing software with minimal support. Video quality was not always ideal with contributing factors being the time of day students used the software. There were no distinguishable time and effort demands associated with the online video conferencing compared to classroom role plays. Some students found use of the technology caused them to feel disconnected from their peers compared to face-to-face encounters, while other students found the encounter more intimate in that the pressure to perform in front of others was not felt. Implications: Video conferencing is a promising tool to facilitate social work role plays. Future research needs to assess the acquisition of specific skills compared to traditional classroom students.